509. FULLY ROBOTIC IVOR-LEWIS ESOPHAGEAL RESECTION (RAMIE) – TECHNICAL DETAILS OF THE RAMIE PROCEDURE IN THE ROBOT2 TRIAL. (24th September 2022) - Grimminger, Peter
Abstract: Robotic-assisted surgery is increasing, especially in cancer surgery. Minimal-invasive esophagectomy (MIE) is commonly the standard operation procedure in high-volume centers. Also, the fully robotic minimally invasive esophagectomy is performed more and more frequent. Over the past 5 years we continuously improved our 4-arm RAMIE procedure. At the moment we are comparing the two total minimal-invasive Ivor-Lewis techniques in a RCT (ROBOT-2 trial). Since January 2017 we perform RAMIE procedures and we would like to demonstrate the further developed robotic technique of one case as an example how we perform Ivor-Lewis RAMIE after a learning case of over 250 RAMIE cases in our case observation center in Mainz Germany. The overall advantages between RAMIE and MIE are under evaluation in our recruiting ROBOT-2 trial, of which we like to report the progress at ISDE 2022.